Hypertension prevalence alteration in 92 815 nurses based on the new standard by 2017 ACC/AHA hypertension guideline: observational cross-sectional study from China. Issue 8 (30th August 2019) - Zhao, Bin; Li, Jing; Liu, Jie; Hao, Yuming; Zhen, Yanjie; Feng, Di; Xu, Menghui; Chen, Ximin; Yang, Xiulan; Zuo, Aifang; Jia, Rufu; Zhang, Ruiqin; et al.
Abstract : Objectives: This study aimed to elucidate the status of hypertension and to analyse the hypertension changes in prevalence, awareness, treatment and control rate among the portion of Chinese nursing staff based on the 2017 American College of Cardiology (ACC)/American Heart Association (AHA) High Blood Pressure Guideline and the 2010 Chinese Guideline for the Management of Hypertension. Design: Cross-sectional study. Setting: 512 medical institutions in 13 cities in Hebei Province. Participants: The candidates of registered nurses from 512 medical institutions in 13 cities in Hebei Province (N=143 772) were invited to participate in the survey, and few of them who refused to participate were excluded from the research group based on the reasons that 93 603 incumbent nurses at the age of 18–65 accepted to the survey and submitted questionnaires online. Undoubtedly, a response rate of 65.11% was achieved. After excluding 788 individuals with incomplete information in the questionnaires, 92 815 participants were included in the final analysis. Main outcome measures: The prevalence, awareness, treatment and control rates of hypertension. Results: 92 815 participants were included in the final analysis, among which consisted of 3677 men (3.96%) and 89 138 women (96.04%). The mean age of the participants was 31.65 (SD=7.47) years. We demonstrated that 26 875 nursing staff were diagnosed as having hypertension according to the new standard by the 2017 ACC/AHA guideline, more than 20 551 cases compared with the previous threshold on the 2010 Chinese guideline. The prevalence of hypertension among nursing staff was 28.96% in the context of the 2017 ACC/AHA guideline, 3.25 times higher than that (6.81%) evaluated by the criteria of the 2010 Chinese guideline. However, the awareness, treatment and control rate (13.50%, 10.73% and 0.81%) were 3.25, 3.22 and 17.48 times lower than those (57.37%, 45.30% and 14.97%) based on the 2010 Chinese guideline, respectively. Conclusions: This research illustrated that it was crucial to improve the awareness rate, drug treatment rate and control rate of hypertension for nurses. Meanwhile, according to the 2017 ACC/AHA guideline, the prevalence of hypertension in China will increase significantly, which poses a more severe challenge to the management of hypertension in China.